Mineral Content of Mangrove Sonneratia alba and Bruguiera gymnorrhiza Fruit Flour - Launda, Pitry; Wonggo, Djuhria; Lohoo, Helen Jenny; Damongilala, Lena J.; Harikedua, Silvana D.; Mentang, Feny (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2023)
Now the mangrove fruit is used and processed into flour to be used as raw materials as well as complementary ingredients with other flour mixtures in certain proportions in making food products. The nutritional content of mangrove processed products can provide information that in addition to being delicious for consumption, mangroves are good for health because they contain nutrients needed by the body. This study aims to analyze calcium, magnesium, potassium, iron and zinc in mangrove fruit flour Sonneratia alba and Bruguiera gymnorhiza. The method used in this study is quantitative. The results showed that mangrove fruit flour sonneratia alba contains levels of calcium 1938.6 mg/100g, magnesium 2136.6 mg/100g, potassium 14688.8 mg/100g, iron 60.7 mg/100g and zinc 1.3 mg / 100g. While mangrove fruit flour Bruguiera gymnorrhiza contains levels of calcium 676.5 mg/100g, magnesium 41.7 mg/100g, potassium 3033.8 mg/100g, iron 12.8 mg/100g and zinc 0.2 mg / 100g. The results showed that the mineral content in mangrove sonneratia alba fruit flour is higher than Bruguiera gymnorrhiza fruit flour. Keywords: Mangrove flour, Sonneratia alba, Bruguiera gymnorrhiza, Mineral. Abstrak Sekarang ini buah mangrove dimanfaatkan dan diolah menjadi tepung untuk digunakan sebagai bahan baku maupun sebagai bahan komplementer dengan campuran tepung lain pada proporsi tertentu dalam membuat produk pangan. Kandungan gizi pada produk olahan mangrove dapat memberikan informasi bahwa selain nikmat untuk dikonsumsi, mangrove baik untuk kesehatan karena mengandung gizi yang dibutuhkan oleh tubuh. Penelitian ini bertujuan untuk menganalisis kalsium, magnesium, kalium, zat besi dan seng pada tepung buah mangrove Sonneratia alba dan Bruguiera gymnorhiza. Metode yang digunakan dalam penelitian ini adalah kuantitatif. Hasil penelitian menunjukkan bahwa tepung buah mangrove Sonneratia alba mengandung kadar kalsium 1938.6 mg/100g, magnesium 2136.6 mg/100g, kalium 14688.8 mg/100g, zat besi 60.7 mg/100g dan seng 1.3 mg/100g. Sedangkan tepung buah mangrove Bruguiera gymnorrhiza mengandung kadar kalsium 676.5 mg/100g, magnesium 41.7 mg/100g, kalium 3033.8 mg/100g, zat besi 12.8 mg/100g dan seng 0.2 mg/100g. Dari hasil penelitian didapatkan bahwa kandungan mineral pada tepung buah mangrove Sonneratia alba lebih tinggi dari tepung buah Bruguiera gymnorrhiza. Kata kunci: Tepung mangrove, Sonneratia alba, Bruguiera gymnorrhiza, Mineral.